Executive pay and firm performance in the Philippines - Unite, Angelo A. (Animo Repository, 2008)
This paper provides the first systematic evidence on the nature of the relation between executive compensation and firm performance in the Philippines. Comparable to studies of Japan, Korea, and China, we find a positive relation between executive compensation and performance in the Philippines for those firms not affiliated to a corporate group, but that this relation does not hold for affiliated firms. We conclude that the substantial portion of the Philippine economy that is under the control of group networks incentivize managers in ways other than through use of pay-performance schemes. © 2007 Elsevier B.V. All rights reserved.